Perancangan User Interface User Experience Aplikasi E-Ngaji Berbasis Android Menggunakan Metode User Centered Design (UCD) Pada TPQ - Adzhal Mahfudh; Wahyu Rizqy Saputra (Jurnal Teknik Informatika UMUS, 2022)
The applications needed today must be practical and have a positive effect on an ongoing basis. This results in the importance of designing User Interface (UI) and User Experience (UX). As Muslims, the challenge that must be observed in this era is to form a generation with Islamic character according to the guidance of Islamic law. The E-Ngaji application is an android-based application as a learning tool for reciting the Koran that pays attention to UI/UX design. An interesting application will make learning to recite at TPQ for children more interactive and not monotonous so that children can absorb the material to the fullest. This article explains how the UI/UX of the E-Ngaji application is designed using the User Centered Design (UCD) method. This application prototype is designed to understand the wishes of the user (users) as the heart of the application design itself. To achieve usability, usability tests were carried out on prototypes using the cognitive walkthrough method. Usability is the key to success and represents user acceptance of an application. scenarios of no more than 30 seconds and errors experienced by participants in using a design is a minor mistake with an error percentage of not more than 50%. This is done so that the application has an attractive interface and is consistent with user satisfaction